Gestão da comunicação das Universidades Federais: mapeamento das ações e omissões - Alves, Cristiano Alvarenga [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The communication sets one of the pillars of the institutions and as such must occupy a strategic place in the organizational structure, in order to disseminate the values and principles and simultaneoulsy contribute to the achievement of objectives and institutional goals. In this context, research on the management of communication of the federal universities aims to verify to what extent the public interest, explained the concept of public communication, and planning, inserted in the definition of organizational communication of federal universities. The analysis was based on four parameters, the search categories: communication policy; communication plan; structure and; activities. To make the data collection, management two documents formed the corpus of research: the Institutional Development Plan (IDP) and the Institutional Self-Assessment Report. The choise of these publications is related to the integration required between the communication, planning and evaluation. The chosen research methodology, content analysis, enables the collection of data from the needs presented by the researcher, that is, from the excerpt of the study. In general, the data collected from the 59 federal universities point to a communciation policy framework and lack of lack of planning for the sector, which compromisses the quality of communication and the relationship with society. This picture was confirmed by crossing with other research sources: the external evaluation reports; data on human resources obtained in the Transparency Portal and; the survey via Citizens Information System (SIC) on the existence communication policy

A comunicação configura um dos pilares das organizações e como tal deve ocupar um lugar estratético na estrutura organizacional, com vistas a disseminar os valores e princípios e, simultaneamente, contribuir com o cumprimento dos objetivos e metas institucionais. Neste contexto, a pesquisa sobre a gestão da comunicações das universidades federais visa verificar em que medida o interesse público, explicitado no conceito de comunicação pública, e o planejamento, inserido na definição de comunicação organizacional, norteiam a Comunicação das universidades federais. A análise foi fundamentada em quatro parâmetros, as categorias de pesquisa: política de comunicação; plano de comunicação; estrutura e atividades realizadas. Para fazer a coleta de dados, dois documentos de gestão formaram o corpus da pesquisa: o Plano de Desenvolvimento Institucional (PDI) e o Relatório de Autoavaliação Institucional. A esolha destas publicações está relacionada à integração necessária entre a Comunicação, o planejamento e a avaliação. A metodologia de pesquisa escolhida, a Análise de Conteúdo, possibilita a coleta de dados a partir das necessidades apresentadas pelo pesquisador, ou seja, a partir do recorte da pesquisa. Em linhas gerais, os dados coletados das 59 universidades federais sinalizam para um quadro de carência de política de comunicação e ausência de planejamento para o setor, o que compromete a qualidade da comunicação e o relacionamento com a sociedade. Esse quadro foi confirmado com o cruzamento com outras fontes de pesquisa: os relatórios de avaliação externa; dados sobre recursos humanos obtidos no Portal Transparência e a pesquisa realizada via Sistema de Informação ao Cidadão (SIC) sobre a existência de política de comunicação
Communication management of Federal Universities: mapping the actions and omissions
Keywords: Comunicação; Gerenciamento da informação; Politica de comunicação; Planejamento da comunicação; Universidades e faculdades; Communication